Ethnobotany and in vitro antimicrobial study of selected medicinal plants used by Magar community in Dhaubadi VDC, Nawalparasi district, Nepal - Nemkul, Chandra Mohini; Shrestha, Ila (Journal of Natural History Museum, 2018)
Magars are one of the oldest tribes in Nepal having indigenous knowledge of health care practices. Dhaubadi VDC is homogenously inhabited with Magars. There are authentic healers and elder people having knowledge of traditional health care practices. Data of traditional knowledge about Oroxylum indicum (L.) Kurz, Premna barbata Wall ex Schaureand Lagestroemia parviflora Roxb. were collected with voucher specimens. Antimicrobial tests of these crude plant extracts were done against Gram positive (Bacillus subtilis and Staphylococcus aureus) and Gram negative (Salmonella typhi, klebsiella pneumoniae andEscherichia coli) bacteria. Aqueous extract of L. parviflora showed antimicrobial test against Gram positive and Gram negative bacteria. Extract of O. indicum showed antimicrobial property against tested bacteria. Leaf extract of P. barbata showed antimicrobial property against S.typhi, S. aureus and E. coli but not to B. subtilis. The result of the research scientifically validated the traditional use of these plants as medicines.